2012
DOI: 10.2337/dc12-0773
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Direct Renin Inhibition Alone and in Combination With ACE Inhibition on Endothelial Function, Arterial Stiffness, and Renal Function in Type 1 Diabetes

Abstract: OBJECTIVEDiabetes is associated with renin-angiotensin system (RAS) activation, leading to renal and systemic vascular dysfunction that contribute to end-organ injury and significant morbidity. RAS blockade with ACE inhibitors reduces, but does not abolish, RAS effects. Accordingly, our aim was to determine if direct renin inhibition alone, and in combination with an ACE inhibitor, corrects early hemodynamic abnormalities associated with type 1 diabetes.RESEARCH DESIGN AND METHODSArterial stiffness (augmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 39 publications
3
30
0
6
Order By: Relevance
“…Whether the protective effect observed with lowsodium diet and RAAS inhibition in this post hoc analysis was due to greater haemodynamic effects, enhanced antiinflammatory effects or both, is unknown and requires further study. Nevertheless, as previously reported by our group [17][18][19] and by other investigators [46], RAAS inhibitors still exert prominent haemodynamic effects on the intrarenal RAAS in the presence of relative RAAS suppression induced by a high-salt diet in diabetic patients. Our results extend this previous haemodynamic-focused body of work by suggesting that RAAS inhibition during salt repletion also reduces inflammatory urinary cytokines/chemokines.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Whether the protective effect observed with lowsodium diet and RAAS inhibition in this post hoc analysis was due to greater haemodynamic effects, enhanced antiinflammatory effects or both, is unknown and requires further study. Nevertheless, as previously reported by our group [17][18][19] and by other investigators [46], RAAS inhibitors still exert prominent haemodynamic effects on the intrarenal RAAS in the presence of relative RAAS suppression induced by a high-salt diet in diabetic patients. Our results extend this previous haemodynamic-focused body of work by suggesting that RAAS inhibition during salt repletion also reduces inflammatory urinary cytokines/chemokines.…”
Section: Discussionsupporting
confidence: 67%
“…Although it is known that RAAS blockade is more effective under conditions of dietary sodium depletion, RAAS inhibitors are still effective in both diabetic and non-diabetic sodium-replete individuals [17][18][19][20]. These observations suggest persistent intrarenal RAAS activation despite high dietary sodium intake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct renin inhibitor monotherapy using aliskiren and combination therapy with ACE inhibitors or calcium blockers improves endothelial function. [15][16][17] Virdis and colleagues reported that aliskiren, compared with ramipril, increased nitric oxide availability in forearm resistance arterioles of patients with essential hypertension. 12 In addition, aliskiren significantly decreased PRA, compared with ramipril, whereas BP, plasma Ang II level, and plasma aldosterone level remained unchanged.…”
Section: Renin Activity and Endothelial Functionmentioning
confidence: 99%
“…Increased leisure time physical activity, weight reduction, avoidance of diatery salt and alcohol abuse as well as increased consumption of diatery heavy chain omega fatty acids as recommended [7]. Drug treatment for arterial hypertension [diuretics, angiotensin-converting enzyme inhibitors (ACE-I), angiotensin-receptor blockers (ARBs), and calcium-channel blockers (CCB)] [8][9][10]; lipid-lowering agents, mainly statins [11,12], hypoglecaemic drugs (thiazolidinediones) [13]; and potentially other novel agents, including AGE breakers [14]. There are been data suggesting that the reduction in AS during treatment for arterial hypertension is not only attributed to the reduction in BP per se but to additional BP loweringindependent effects of antihypertensive drugs [15].…”
mentioning
confidence: 99%